Estudio definitivo para el diseño geométrico de la carretera manteca – La Florida – Alto Uchiza km. 0+000 – km. 12+277.2 - Delgado Hidalgo, Luis (2011)
The current Thesis was chosen for Professional Title of Civil Engineer, has been developed with the purpose of carrying out a contribution technical-scientist to contribute to salve a problem of local variety that to the executed being will allow to tell on a wagon section that it will help to the socioeconomic development of the benefited population. The investigation type is applied and it has been carried by the Faculty of Civil Engineering, of the National University of San Martín, developing the project in the Province of Mariscal Cáceres, Region of San Martín. This work has been developed applying on the land the theories and existing norms of topography, ground mechanics, environmental impact, hydrology, road, concrete drainage and other relatives by marriage, and that have allowed to count on the definitive study of the highway already named. The results demonstrate evidently that it is possible to achieve, from the proper application of the theories, studies and alternative results convincing, that after a judicious analysis can be presented in final draft form, evaluating the feasibility of the whole context, optimizing the road. This, actually means that the elaborated project had an evaluation of alternative routes having itself determined but the optimal one and settling down the most advisable budget, which gives a feasible project us to execute, putting it to disposition of which it corresponds, to transact its financing and execution, doing possible that the National University of San Martín executes it's contribution in favor of the Sanmartinense society.